Modernization and political actions in the Brazilian Amazon : the City of Barcarena, Pará - Nahum, João Santos (SpringerBriefs in Latin American studies., 2017)
This book offers an analysis of the territory of Barcarena, in the Brazilian Amazon. The author studies the land use and the implemented modernization policies that made it one of the richest cities of the state. The political system uses this territory as a resource to provide for the needs of a small circle of social agents. A system of conservative political actions enforces the process of modernization of the Baracena territory. Innovations in the Barcarena territory, such as the implementation of the aluminium factory Albras/Alunorte and the territorial configuration or public administration, lead to modernization simulations and artificial devices. The intended effect however is more about appearing to be modern, than actual modernization. The territorial use of Barcarena is aimed to protect the interests and privileges of the elite.